2005
DOI: 10.1029/2004jd004545
|View full text |Cite
|
Sign up to set email alerts
|

On the fine structure of thunderstorms leading to the generation of sprites and elves: Fractal analysis

Abstract: [1] The fine structure of convective clouds leading to the generation of sprites and elves has been studied using radar images. Sprites and elves were observed on two days, 19 December 1998 and 27 January 1999, in lightning during winter thunderstorms on the Sea of Japan. Fractal analyses of the radar images (as an ensemble and as separate clusters) for those two days have been performed with respect to the occurrence of sprites and elves. We have found that a sprite and/or an elve is triggered when and just a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
20
0

Year Published

2006
2006
2018
2018

Publication Types

Select...
7
3

Relationship

3
7

Authors

Journals

citations
Cited by 21 publications
(21 citation statements)
references
References 32 publications
1
20
0
Order By: Relevance
“…(1) First we summarise the morphological characteristics of winter sprites during this campaign as compared with our previous works (Hobara et al, 2001;Hayakawa et al, 2004bHayakawa et al, , 2005Nakamura and Hayakawa, 2004). Before we have observed only a simple structure; that is, columnar structure (sometimes a single column, but sometimes a couple of columnar shapes).…”
Section: Article In Pressmentioning
confidence: 93%
“…(1) First we summarise the morphological characteristics of winter sprites during this campaign as compared with our previous works (Hobara et al, 2001;Hayakawa et al, 2004bHayakawa et al, , 2005Nakamura and Hayakawa, 2004). Before we have observed only a simple structure; that is, columnar structure (sometimes a single column, but sometimes a couple of columnar shapes).…”
Section: Article In Pressmentioning
confidence: 93%
“…The cloud size associated with the À20°C isotherm was between 8,500 and 40,500 km 2 , which was smaller than the usual sprite-parent summer MCSs (greater than 20-25,000 km 2 ) in large continents [Adachi et al, 2005]. Hayakawa et al [2004Hayakawa et al [ , 2005 discussed why such small winter thundercloud systems are able to generate spriteinducing lightning. They concluded that many small thunderstorm cells were connected with each other and the connection enabled large electric charge transfer to induce sprites.…”
Section: Introductionmentioning
confidence: 94%
“…Fractal approach to modeling of a lightning discharge was implemented by several groups of authors [4,7,[18][19][20]. In all of their papers, they solve numerically the problem of the leader channel development within the framework of a Poisson three-dimensional equation with allowance for the external field and the use of a stochastic model of the dielectric breakdown, which dates back to fundamental works [21][22][23].…”
Section: Introductionmentioning
confidence: 99%